Acylated and Desacylated Ghrelin, Preptin, Leptin, and Nesfatin-1 Peptide Changes Related to the Body Mass Index - Ozkan, Yusuf; Timurkan, Esra Suay; Aydin, Suleyman; Sahin, Ibrahim; Timurkan, Mustafa; Citil, Cihan; Catak, Zekiye (Hindawi Ltd, 2013)
This study examines the levels of acylated and desacylated ghrelin, preptin, leptin, and nesfatin-1 peptide changes related to the body mass index (BMI). The subjects were allocated to 5 groups depending on their BMIs as follows: Group I (BMI < 18.5 kg/m(2)); Group II (BMI 18.5-24.9 kg/m(2)); Group III (BMI 25-29.9 kg/m(2)); Group IV (BMI 30-39.9 kg/m(2)); Group V (BMI > 40 kg/m(2)). Serum acylated and desacylated ghrelin, preptin, and leptin levels were measured by the enzyme-linked immunosorbent assay (ELISA) and nesfatin-1 was measured by the enzyme immunoassay (EIA). Desacylated ghrelin levels showed a gradual and statistically significant drop from Group I to Group V, while preptin and leptin levels exhibited a gradual and significant increase from Group I to Group IV. Serum nesfatin-1 levels gradually, but not significantly, increased from Group I to Group III and showed a significant decrease in Groups IV and V. In conclusion, leptin, preptin, and acylated ghrelin (AG) levels increased with higher BMI, whereas desacylated ghrelin (DAG) decreased and nesfatin-1 showed no clear relationship to BMI.
Keywords: Bound Leptin; Insulin; Obesity; Hormone; Identification; Prevalence; Cells